Postmodernism and Commercialization of Vernacular Architecture: Spatial Hierarchy in Indonesian Traditional Houses - Prayitno, Aryasatya Rafa (Departement of Architecture, Universitas Islam Indonesia, 2026)
Societies continuously move toward what is perceived as a “better” condition. From myth to reason, from geocentrism to heliocentrism, and from colonization to revolution, these shifts mark fundamental changes in how societies construct knowledge and meaning. This study examines the influence of postmodernism and commercialization on vernacular architecture in Indonesia, with a specific focus on the transformation of spatial hierarchy within traditional houses. Using a qualitative and interpretative approach, the research analyzes how postmodern architectural ideals, such as plurality, symbolism, and contextual expression interact with market-driven pressures in shaping contemporary adaptations of vernacular forms. The study focuses on Indonesian traditional houses, particularly Joglo and Batak Toba dwellings, while selected postmodern architectural works are employed as a theoretical framework rather than primary objects of analysis. The findings indicate that commercialization not only affects architectural form and materiality but also reconfigures spatial hierarchy, altering traditional distinctions between sacred and profane, public and private, and central and peripheral spaces. This study argues that understanding changes in spatial hierarchy is crucial for critically assessing the impact of postmodernism and commercialization on vernacular architecture, and for addressing the challenges of preserving cultural meaning within evolving urban and socio-economic contexts.